2012
DOI: 10.2478/v10045-012-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Flight Dynamics of Ostrinia Nubilalis HBN. (Lep., Crambidae) Based on the Light and Pheromone Trap Catches in Nienadówka (South-Eastern Poland) in 2006-2008

Abstract: Abstract:The experiment was conducted in the 2006-2008 time period, in Nienadówka near Rzeszów, Poland (50°11' N, 22°06' E). The high suitability of light traps for the monitoring of Ostrinia nubilalis Hbn. moth flights on maize fields was shown. These light traps were compared to the pheromone types of traps; the "delta" model, and the "funnel" with a pheromone dispenser containing Z-11-tetradecenyl acetate (series ONC036A and ONC048A/107). In the light trap, the first moths were found in the second decade or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
0
7
0
11
Order By: Relevance
“…Higher temperatures accelerate the development of insects and thus increase the population . In a study carried out between 2006 and 2009, Bereś observed that rainfall, strong winds, and large temperature fluctuations, if occurring during the mating period, significantly decrease their activity . In a study carried out in Slovenia in hops plantations, Cizej and Trematerra found a similar effect of weather on the flight of O. nubilalis adult moths and observed that the average daily temperature and the weekly rainfall were the factors of greatest impact on the insect's flight patterns.…”
Section: Discussionmentioning
confidence: 94%
“…Higher temperatures accelerate the development of insects and thus increase the population . In a study carried out between 2006 and 2009, Bereś observed that rainfall, strong winds, and large temperature fluctuations, if occurring during the mating period, significantly decrease their activity . In a study carried out in Slovenia in hops plantations, Cizej and Trematerra found a similar effect of weather on the flight of O. nubilalis adult moths and observed that the average daily temperature and the weekly rainfall were the factors of greatest impact on the insect's flight patterns.…”
Section: Discussionmentioning
confidence: 94%
“…W badaniach Żołnierza i Hureja (2007) oraz Beresia (2012c) liczba złapanych motyli w samołówkach była nieporównywalnie większa (w szczycie liczebności nawet powyżej 300 motyli/dzień obserwacji) niż w pułapkach feromonowych, w których autorzy stwierdzali zwykle tylko pojedyncze osobniki (zwykle w liczbie nie przekraczającej 10 motyli/dzień obserwacji). Ponadto w latach 2006-2008 pułapki świetlne pozwoliły wykryć w drugiej połowie września lot najprawdopodobniej drugiego pokolenia szkodnika (Żołnierz i Hurej 2007;Bereś 2012c).…”
Section: Monitoring Występowania O Nubilalis W Polsce -Stan Aktualnyunclassified
“…Nie bez znaczenia jest także sposób prowadzenia uprawy, a w szczególności stosowanie uproszczeń agrotechnicznych, w tym wieloletniej monokultury (Bereś i Pruszyński 2008). Ponadto, korzystny układ warunków klimatycznych sprzyja rozwojowi omacnicy prosowianki, która w niektóre lata rozwija drugie, mało liczne pokolenie (Żołnierz i Hurej 2007;Bereś 2012). Brak wystarczającej liczby insektycydów (zwłaszcza o działaniu niezależnym od temperatury) i biopreparatów oraz specjalistycznych opryskiwaczy szczudłowych utrudnia skuteczną walkę ze szkodnikiem.…”
Section: Efektywność Działania Kukurydzy Zmodyfikowanej Genetycznie Nunclassified